ADVANTAGES OF USING ELECTRONIC RESOURCES IN THE MODERN EDUCATIONAL PROCESS - Sartbayeva, Zh.; Abduakassov, А. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
With the rapid development of information technology and resources, the teaching process has reached a new level. Today, electronic tools have become a reliable companion of the teacher. Integration of technologies in education is one of the actual topics of research in modern education. This article deals with the issue of evaluating the effectiveness of digital technologies and electronic resources used in modern education based on science teaching.
Keywords: process modeling; interactivity; network distribution; e–learning resources; digital technologies; e–textbooks